Opposite responses by different chemoreceptors set a tunable preference point in Escherichia coli pH taxis - Yang, Yiling; Sourjik, Victor (Molecular microbiology, 2012)
In bacterial habitats, the ability to follow spatial gradients of environmental factors that affect growth and survival can be largely advantageous. The bacterial strategy for unidirectional chemotactic movement in gradients of typical attractants or repellents, such as nutrients or toxins, is well understood. Optimal levels of other factors, however, may be found at intermediate points of a gradient and thus require a bidirectional tactic movement towards the optimum. Here we investigate the chemotactic response of Escherichia coli to pH as an example of such bidirectional taxis. We confirm that E. coli uses chemotaxis to avoid both extremes of low and high pH and demonstrate that the sign of the response is inverted from base-seeking to acid-seeking at a well-defined value of pH. Such inversion is enabled by opposing pH sensing by the two major chemoreceptors, Tar and Tsr, such that the relative strength of the response is modulated by adaptive receptor methylation. We further demonstrate that the inversion point of the pH response can be adjusted in response to changes in the cell density.
First published: 18 October 2012
Gesehen am 21.06.2018